Effectiveness of Dash Diet (Dietary Approach to Stop Hypertension) Education on The Level of Knowledge in Preventing Hypertension in The Elderly at The Kedungwungu Public Health Center - Nurapipah, Maulida; Wardin, Ito; Harun; Wardiyanto, Yayan (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Hypertension is a condition in which a person experiences an increase in blood pressure exceeding the normal limit, which is more than 140/90 mmHg. One non-pharmacological therapy for hypertension sufferers is providing education on the DASH diet. The DASH diet (Dietary Approach to Stop Hypertension) is a diet to lower blood pressure in hypertensive patients, or a diet to reduce salt consumption and consume foods containing high sodium. This study aims to determine the effectiveness of DASH diet education on the level of knowledge in preventing hypertension in the elderly at the Kedungwungu Community Health Center. This study used a quasi-experimental design with a pre- and post-test design with one group. The research instrument used a record sheet in the form of a questionnaire about DASH diet knowledge. Results : The results of the Wilcoxon test produced a Z test statistic of -4.301 with a significance value of 0.000, stating that DASH diet education was significantly proven to be effective in increasing the level of knowledge in preventing hypertension before and after being given DASH diet education. Conclusion : Providing DASH Diet education has proven to be very effective in increasing the knowledge of elderly people with hypertension. Suggestion : It is hoped that DASH diet education can be implemented comprehensively in health services.